2017
DOI: 10.1002/ajhb.22972
|View full text |Cite
|
Sign up to set email alerts
|

Weight, gender, and depressive symptoms in South Korea

Abstract: ObjectivesObesity consistently predicts depression risk, but the underlying mechanisms are poorly understood. Body concerns are proposed as key. South Korean society is characterized by extremely high levels of explicit weight stigma, possibly the highest globally. Using cross‐sectional Korean 2014 National Health Examination Survey (KNHANES) data, we test this proposition in a nationally representative sample of South Korean adults (N = 5,632).MethodsDepressive symptoms (outcome variable), was based on the PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
5
36
1
Order By: Relevance
“…Obesity was positively associated with having inappropriately short sleep duration in both men and women, while statistically significant association between weight status and sleep quality was not detected in both genders. Previous studies reported gender differences in overweight/obesity and sleep problems [60][61][62]. In general, male college students have higher prevalence of overweight/obesity compared to their female counterparts in both the U.S. [60] and Korea [61].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Obesity was positively associated with having inappropriately short sleep duration in both men and women, while statistically significant association between weight status and sleep quality was not detected in both genders. Previous studies reported gender differences in overweight/obesity and sleep problems [60][61][62]. In general, male college students have higher prevalence of overweight/obesity compared to their female counterparts in both the U.S. [60] and Korea [61].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies reported gender differences in overweight/obesity and sleep problems [60][61][62]. In general, male college students have higher prevalence of overweight/obesity compared to their female counterparts in both the U.S. [60] and Korea [61]. In contrast, female college students are more likely to experience sleep problems than their male counterparts in both countries [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Japan is a high-income, developed country, whereas South Korea and Taiwan are high-income developing countries and China is an upper-middle-income developing county [ 18 , 20 ]. People feel pressured by adhering to social norms of being ‘thin’ and stressed by weight-related stigma as the country has advanced [ 21 23 ]. Stigma in weight ultimately led to more negative physical and psychological health outcomes [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…People feel pressured by adhering to social norms of being ‘thin’ and stressed by weight-related stigma as the country has advanced [ 21 23 ]. Stigma in weight ultimately led to more negative physical and psychological health outcomes [ 21 23 ]. Recent studies found that stigma against weight (“anti-fat cultural context [ 21 ]”) was extremely high in South Korea [ 21 , 24 26 ] and Japan [ 27 , 28 ], but Chinese were more tolerant about overweight/obesity [ 9 , 24 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, 38.3% of men and 41.6% of women in the U.S. in the same year and 31.5% of men and 29.3% of women in Australia in 2017 were estimated to be clinically obese in the same year (data available at http://stats.oecd.org). Yet, despite the extremely low population levels of obesityor perhaps even because of it -anti-fat sentiment is reportedly now rampant in South Korea (Marini et al, 2013;Brewis et al, 2017;Noh et al, 2018). It is common to notice disparaging treatment of people with obesity in Korean media (Lim and Kim, 2012).…”
Section: Resultsmentioning
confidence: 99%